Gnathia marleyi sp. nov. (Crustacea, Isopoda, Gnathiidae) from the Eastern Caribbean - Farquharson, Charon; Smit, Nico J.; Sikkel, Paul C. (Zootaxa, 2012)
A new species of gnathiid was collected in June-August 2008 and 2009 from various sites in the Eastern Caribbean. Third stagepranizae taken from fish hosts were maintained in fresh sea water until their moult into males or females. Distinctive features ofthe adult male cephalosome include a produced frontal border with conical superior fronto-lateral processes and a slightly sunkeninferior conical medio-frontal process. The male mandible is 0.8 times the length of cephalosome with 10 to 11 processes ondentate blade. The adult female has a rectangular cephalosome with convex lateral margins, 1.2 times as wide as long with noparaocular ornamentation. The female frontal border is broadly rounded, produced and slightly concave anteriorly. The third stage praniza is characterised by a mandible with 8 large, triangular teeth, directed backwardly and 2 small teeth at the tip.